"Deep-Dive analysis of the latest Lithium-Ion battery safety testing standards and regulations in Germany and China". (March 2023) - Lin, C.; Burggräf, P.; Liu, L.; Adlon, T.; Mueller, K.; Beyer, M.; Xu, T.; Kammerer, V.; Hu, J.; Liu, S.; Wang, F.
Abstract: Lithium-Ion batteries contribute a key technology for electric vehicles. Their production is being accelerated worldwide as electric vehicles become increasingly popular – not only because of the tremendous challenges of climate change. Currently, the homologation of Lithium-Ion batteries is subject to different regulations and authorities in different markets, provoking high efforts for battery testing in general. This comprehensive comparison of the latest updated Chinese regulation GB 38031–2020 with German as well as UN and ECE standards and regulations aims at exploring potentials for their harmonization. For this purpose, testing methods in the corresponding standards and regulations are systematically categorized, matched and evaluated. It is found that the testing methods for vibration, crush, altitude and pressure, thermal propagation and water immersion safety show the greatest differences. In corresponding deep dives, those testing methods are examined and challenged with regard to realistic vehicle usage situations and suggestions for further improvements are being derived. Finally, the authors discuss possible harmonization approaches, taking into account upcoming battery technological developments. Highlights: GB 38031 is compared for the first time with German, UN and ECE standards and regulations. An approach for the comparison of testing methods in standards & regulations is proposed. A deep-dive analysis on safety testing methods regarding harmonization potentials is conducted. Guidelines for the harmonization of battery testing methods and test execution are derived.